Chronic stress and moderate physical exercise prompt widespread common activation and limited differential activation in specific brain regions. (October 2016) - Kim, Tae-Kyung; Han, Pyung-Lim
Abstract: Chronic stress in rodents produces depressive behaviors, whereas moderate physical exercise counteracts stress-induced depressive behaviors. Chronic stress and physical exercise appear to produce such opposing effects by changing the neural activity of specific brain regions. However, the detailed mechanisms through which the two different types of stimuli regulate brain function in opposite directions are not clearly understood. In the present study, we attempted to explore the neuroanatomical substrates mediating stress-induced behavioral changes and anti-depressant effects of exercise by examining stimulus-dependent c-Fos induction in the brains of mice that were exposed to repeated stress or exercise in a scheduled manner. Systematic and integrated analyses of c-Fos expression profiles indicated that various brain areas, including the prelimbic cortex, lateral septal area, and paraventricular nuclei of hypothalamus were commonly and strongly activated by both stress and exercise, while the lateral habenula and hippocampus were identified as being preferentially activated by stress and exercise, respectively. Exercise-dependent c-Fos expression in all regions examined in the brain occurred in both glutamatergic and GABAergic neurons. These results suggest that chronic stress and moderate exercise produce counteractive effects on mood behaviors, along with prompting widespread common activation and limited differential activation in specific brain regions. Highlights: Stress and exercise produce opposing effects on mood behaviors in mice. Stress and exercise promote widespread common activation in the brain. Stress and exercise produce limited differential activation in specific brain regions.